2017
DOI: 10.1136/bjsports-2016-096996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in support of the call to ban the tackle and harmful contact in school rugby: a response to World Rugby

Abstract: In a paper published in BJSM (June 2016), World Rugby employees Ross Tucker and Martin Raftery and a third coauthor Evert Verhagen took issue with the recent call to ban tackling in school rugby in the UK and Ireland. That call (to ban tackling) was supported by a systematic review published in BJSM. Tucker et al claim that: (1) the mechanisms and risk factors for injury along with the incidence and severity of injury in youth rugby union have not been thoroughly identified or understood; (2) rugby players are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The injury epidemiology of players at the community level of the sport, and especially of female players, has been investigated in relatively few research studies [6][7][8][9][10][11]. Some researchers and safety advocates have suggested that injury surveillance in youth rugby is not as comprehensive as it ought to be, and the relative lack of research on the risks of injury for community-level players, especially for children, has led to competing claims about whether rugby is an acceptably safe sport [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The injury epidemiology of players at the community level of the sport, and especially of female players, has been investigated in relatively few research studies [6][7][8][9][10][11]. Some researchers and safety advocates have suggested that injury surveillance in youth rugby is not as comprehensive as it ought to be, and the relative lack of research on the risks of injury for community-level players, especially for children, has led to competing claims about whether rugby is an acceptably safe sport [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Succinctly, children and young people are not able to impact the decisions that affect them in the rugby terrain through structural barriers. Indeed, this is increasingly pertinent given the current social concern around injury and brain trauma within the sporting context (Mez et al 2017, Pollock, White and Kirkwood 2017, White, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2016, we have been strong advocates for the removal of tackling from rugby (League and Union) played in school physical education in the UK 1. This is because (A) tackling is the leading cause of injury in rugby, (B) rugby has a level of risk that is higher than non-contact sports, (C) there is no requirement or need for tackling as part of the school physical education curriculum, and (D) many children are compelled to participate in contact rugby 2.…”
Section: The Call To Ban Tackling In Physical Education Rugbymentioning
confidence: 99%